Influence of Abutment Type and Esthetic Veneering on Preload Maintenance of Abutment Screw of Implant-Supported Crowns - Delben, Juliana Aparecida; Barão, Valentim Adelino Ricardo; Santos, Paulo Henrique dos [UNESP]; Assunção, Wirley Goncalves [UNESP] (Wiley, 2013)
Purpose: The effect of veneering materials on screw joint stability remains inconclusive. Thus, this study evaluated the preload maintenance of abutment screws of single crowns fabricated with different abutments and veneering materials. Materials and Methods: Sixty crowns were divided into five groups (n = 12): UCLA abutment in gold alloy with ceramic (group GC) and resin (group GR) veneering, UCLA abutment in titanium with ceramic (group TiC) and resin (group TiR) veneering, and zirconia abutment with ceramic veneering (group ZiC). Abutment screws made of gold were used with a 35 Ncm insertion torque. Detorque measurements were obtained initially and after mechanical cycling. Data were analyzed by ANOVA and Fisher's exact test at a significance level of 5%. Results: For the initial detorque means (in Ncm), group TiC (21.4 ± 1.78) exhibited statistically lower torque maintenance than groups GC (23.9 ± 0.91), GR (24.1 ± 1.34), and TiR (23.2 ± 1.33) (p < 0.05, Fisher's exact test). Group ZiC (21.9 ± 2.68) exhibited significantly lower torque maintenance than groups GC, GR, and TiR (p < 0.05, Fisher's exact test). After mechanical cycling, there was a statistically significant difference between groups TiC (22.1 ± 1.86) and GR (23.8 ± 1.56); between groups ZiC (21.7 ± 2.02) and GR; and also between groups ZiC and TiR (23.6 ± 1.30) (p < 0.05, Fisher's exact test). Conclusions: Detorque reduction occurred regardless of abutment type and veneering material. More irregular surfaces in the hexagon area of the castable abutments were observed. The superiority of any veneering material concerning preload maintenance was not established. © 2013 by the American College of Prosthodontists.
Keywords: Abutment; Implant-supported prosthesis; Preload; Screw; Veneering material